2008
DOI: 10.1212/01.wnl.0000310646.32212.3a
|View full text |Cite
|
Sign up to set email alerts
|

Impaired insulin secretion increases the risk of Alzheimer disease

Abstract: In this longitudinal study, impaired acute insulin response at midlife was associated with an increased risk of Alzheimer disease (AD) up to 35 years later suggesting a causal link between insulin metabolism and the pathogenesis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(151 citation statements)
references
References 31 publications
6
140
1
4
Order By: Relevance
“…In the present study, EIR was measured in an OGTT at 71 years. The findings of an association between impaired EIR and Alzheimer's disease in the present study are in line with our previous report, in which the impaired acute insulin response measured at an intravenous glucose tolerance test at age 50 was associated with Alzheimer's disease later in life [9]. Thus, this risk marker is stable at both middle and higher ages and can be detected in an OGTT, although this method is less reproducible than an intravenous glucose tolerance test.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, EIR was measured in an OGTT at 71 years. The findings of an association between impaired EIR and Alzheimer's disease in the present study are in line with our previous report, in which the impaired acute insulin response measured at an intravenous glucose tolerance test at age 50 was associated with Alzheimer's disease later in life [9]. Thus, this risk marker is stable at both middle and higher ages and can be detected in an OGTT, although this method is less reproducible than an intravenous glucose tolerance test.…”
Section: Discussionsupporting
confidence: 92%
“…The association between low EIR and Alzheimer's disease was stronger in men without the APOE ε4 allele than in those with this allele, confirming our previous results from this population [9]. An impaired insulin response seems to be an important risk factor for Alzheimer's disease in the absence of the high-risk allele.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A longitudinal study on 2,322 participants, followed up for 32 years reported that impaired insulin response in midlife was associated with an increased risk of AD [61]. Van Oijen and colleagues reported CD in older women with high levels of fasting insulin secretion in midlife, in comparison to those with lower levels of insulin secretion [62].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, borderline conditions, prediabetes or impaired glucose tolerance are also related to an increased risk of AD and other dementias in very old people 75 . This relationship may be partly explained by diabetic comorbidities such as hypertension and dyslipidaemia [76][77][78] . A relationship was also found between a higher prevalence of AD in an elderly population in Finland 79 , although an analytical study of a multiethnic cohort of the elderly in the USA found no association between the metabolic syndrome and either the prevalence or incidence of AD, despite the fact that two components of the syndrome, i.e.…”
Section: Diabetes Mellitusmentioning
confidence: 99%